Novel GLP-1 Analog Supaglutide Reduces HFD-Induced Obesity Associated with Increased Ucp-1 in White Adipose Tissue in Mice - Wan, Yun; Bao, Xi; Huang, Jiabao; Zhang, Xiangyu; Liu, Wenjuan; Cui, Qiaoli; Jiang, Dongdong; Wang, Zhihong; Liu, Rui; Wang, Qinghua (Frontiers in Physiology, 2017)
GLP-1, an important incretin hormone plays an important role in the regulation of glucose homeostasis. However, the therapeutic use of native GLP-1 is limited due to its short half-life. We recently developed a novel GLP-1 mimetics (supaglutide) by genetically engineering recombinant fusion protein production techniques. We demonstrated that this formulation possessed long-lasting GLP-1 actions and was effective in glycemic control in both type 1 and type 2 diabetes rodent models. Here, we investigated the effects of supaglutide in regulating energy homeostasis in obese mice. Mice were fed with high-fat diet (HFD) for 6 months to induce obesity and then subjected to supaglutide treatment (300μg/kg, bi-weekly for 4weeks), and placebo as control. Metabolic conditions were monitored and energy expenditure was assessed by indirect calorimetry (CLAMS). Cold tolerance test was performed to evaluate brown-adipose tissue (BAT) activities in response to cold challenge. Glucose tolerance and insulin resistance were evaluated by intraperitoneal glucose tolerance test and insulin tolerance tests. Liver and adipose tissues were collected for histology analysis. Expression of uncoupling protein 1(Ucp1) in adipose tissues was evaluated by Western blotting. We found that supaglutide treatment reduced body weight, which was associated with reduced food intake. Compared to the placebo control, supaglutide treatment improved lipid profile, i.e., significantly decreased circulating total cholesterol levels, declined serum triglyceride and free fatty acid levels. Importantly, the intervention significantly reduced fatty liver, decreased liver triglyceride content, and concomitantly ameliorated liver injury exemplified by declined hepatic alanine aminotransferase (ALT) and aspartic transaminase (AST) content. Remarkably, supaglutide reduced hepatic lipid accumulation and altered morphometry in favor of small adipocytes in fat. This is consistent with the observation that supaglutide increased tolerance of the mice to cold environment associated with up-regulation of Ucp1 in the inguinal fat. Furthermore, supaglutide improved glucose tolerance and insulin sensitivity in the obese mice suggesting improved glucose and energy homeostasis. Our findings suggest that supaglutide exerts beneficial effect on established obesity through reducing energy intake and is associated with brown remodeling of white adipose tissue.